NILAI EKONOMI WISATA CURUG PUTRI TAMAN HUTAN RAYA BANTEN PROVINSI BANTEN - Nazma, Fathia; Lidiawati, Ina; Rusli, Abdul Rahman (Jurnal Nusa Sylva, 2024)
Banten Forest Park has several natural tourist attractions, one of which is Curug Putri. Curug Putri can be used as a natural tourist attraction and non-timber forest product and if managed well will have economic value. The aim of the research is to determine the economic value of the tourist destination Curug Putri Taman Hutan Raya Banten and examine the influence of visitor income, travel costs and distance traveled on the quantity of visitors to the tourist destination Curug Putri Taman Hutan Raya Banten. Multiple linear regression and the travel cost approach or TCM (Travel Cost Method) are the research methods used. The results of research using the travel cost approach showed that the economic value of Curug Putri Taman Hutan Raya Banten tourism was IDR 4,796,378,496/year. The regression equation shows that visitor income, travel costs, and distance traveled influence the number of visits: Y = 2.431 + 0.362X1 + (- 0.535X2) + 0.333X3. Visitor income (X1) has a value of 0.362. Which means that if there is a one unit increase in visitor income, visitors will make a return visit of 0.362, the distance traveled (X2) is -0.535. This means that if the distance increased by 100 km, there will be a decrease in the number of visits by -0.535, while for transportation costs (X3) the value is 0.333, meaning that if transportation costs increase, the number of visits will increase by 0.333 assuming the other independent variables are considered constant/paribus paribus. After partial testing of all independent variables, only the travel distance variable had a significant effect on the number of visits.